Pengembangan Instrumen Penilaian Kerja Laboratorium Fisika untuk Mengukur Sikap dan Tanggung Jawab Siswa - Sulistiyono Sulistiyono; Mundilarto Mundilarto; Heru Kuswanto (Jurnal Materi dan Pembelajaran Fisika, 2019)
This research aims to produces a work assessment instruments for effective physics laboratory and is able to measure the attitude of discipline and responsibility of students. The methods used in this research is the research development (R&D) The subject of research used in this students of class X SMA N Margabaru, SMA N Megang Sakti, SMA YPBI 3 Tugumulyo. Processing of data in this study conducted in a qualitative descriptive. The results showed that (1) a workplace assessment instrument decent physics laboratory used to measure attitudes and responsibilities of students based on the results of the validation of the experts included in the category either (2) attitude of discipline students get average 86.2 included in katogori very well, while for the responsibility of the students getting an average 90.7 belong in the category. So a work assessment instrument physics laboratory to effectively measure student attitudes and responsibilities when implementing the activities of the physics laboratory.